2020
DOI: 10.1039/d0cp00158a
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of Mg2+conduction in ammine magnesium borohydride promoted by a neutral molecule

Abstract: Light weight and cheap electrolytes with fast multi-valent ion conductivity can pave the way for future high-energy density solid-state batteries, beyond the lithium-ion battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
125
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(144 citation statements)
references
References 32 publications
12
125
0
Order By: Relevance
“…Elaborating the influence of amorphous Mg(BH 4 ) 2 on the conduction process has recently been published [10]. In addition, Jensen et al demonstrated a conductivity of σ = 3.3 × 10 −4 S cm −1 at T = 353 K for Mg(BH 4 ) 2 •NH 3 [11]. The conclusions of this work in connection with an earlier study [12] suggest a novel ion conduction mechanism in these materials [11].…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Elaborating the influence of amorphous Mg(BH 4 ) 2 on the conduction process has recently been published [10]. In addition, Jensen et al demonstrated a conductivity of σ = 3.3 × 10 −4 S cm −1 at T = 353 K for Mg(BH 4 ) 2 •NH 3 [11]. The conclusions of this work in connection with an earlier study [12] suggest a novel ion conduction mechanism in these materials [11].…”
supporting
confidence: 64%
“…In addition, Jensen et al demonstrated a conductivity of σ = 3.3 × 10 −4 S cm −1 at T = 353 K for Mg(BH 4 ) 2 •NH 3 [11]. The conclusions of this work in connection with an earlier study [12] suggest a novel ion conduction mechanism in these materials [11]. In general, the work on Mg 2+ conductors and especially M-B-N-H systems (M = Li, Mg) has a positive impact on material properties thus increasing their potential as new battery materials [13][14][15][16].…”
mentioning
confidence: 99%
“…15 Very recent studies have shown the possibility to reach high ionic conductivities of about 10 -5 S.cm -1 close to room temperature by adding neutral molecules to Mg(BH4)2. In this manner, Mg(en)1(BH4)2 with en being ethylene-diamine, Mg(BH4)2-NH3 and Mg(BH4)2(NH3BH3)2 reach ionic conductivities of 6x10 -5 S.cm -1 at 70°C, 16 8.5x10 -5 S.cm -1 at 70°C, 17 and 8.4x10 -5 S.cm -1 at 40°C, 18 respectively. The latter is indeed the solid compound with the highest Mg 2+ ionic conductivity reported so far.…”
Section: Spectroscopymentioning
confidence: 94%
“…Such a design can be done by combining NH 3 (or N 2 H 4 ) molecules with BH 4 À anions for example, [36][37] as for ammonium calcium tetra-borohydride NH 4 Ca(BH 4 ) 4 , [38] and ammine magnesium borohydride Mg(BH 4 ) 2 ⋅ NH 3 . [39] The third example is about the dihydrogen H δ + ⋅⋅⋅H δÀ bond-driven dehydrocoupling of amine boranes into polyaminoborane and borazine-linked polymeric structures. [17][18][19][20][21][22] Dihydrogen H δ + ⋅⋅⋅H δÀ bonds have not been used to their full potential.…”
Section: Introductionmentioning
confidence: 99%